Neurotoxic effect in lactating mice pups received oseltamivir phosphate (tamiflu) through milk from dosed nursing mothers during lactation period - Abass, Duraid A.; Rasheed, Emad M.; Abass, Areej B. (The Iraqi Journal of Veterinary Medicine, 2012)
The present study was aimed to evaluate neurotoxic effects of oseltamivir phosphate in lactating pups of orally dosed mice mothers during lactation. Twelve recently parturited female albino mice were divided equally into three groups, one control and two treated groups, each group consists of 4 dosed dams and 8 chosen pups .The nursing dams of T1 and T2 dosed daily orally with 1mg/kg and 5mg/kg,oseltamivir phosphate respectively representing the therapeutic dose and 5 fold dose of drug while control group dosed with distilled water. Lactating mice pups of all groups examined for the following parameters: First parameter was body weight changes and gain: In which T1group showed significant increase in mice pups body weight gain after 14 day of treatment in comparison with control group and T2. Second parameter was clinical symptoms observation /daily, all treatment groups that showed neurotoxic symptoms appeared from 1st dose and extended along the next few days of treatment to be gradually disappeared and completely lost within the last days of treatment in dose dependent manner.These neurotoxic symptoms were weakness, convulsions ,lay on back or side, extended body, incoordination ,extended limbs and limbs stiffness. Third parameter was gross and histopathological studies which demonstrate that the brain was the most affected organ beside extensive lesions in liver, kidney, stomach and small intestine of treated groups in dose dependent manner.In conclusion of this study revealed that Oseltamivir phosphate produce neurotoxic effect in mice pups through indirect administration by nursing mothers dosing during lactation period and the level of toxicity was in dose dependent manner.